1992
DOI: 10.1002/j.1460-2075.1992.tb05101.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical demonstration of complex formation of histone pre-mRNA with U7 small nuclear ribonucleoprotein and hairpin binding factors.

Abstract: Histone RNA 3′ end formation occurs through a specific cleavage reaction that requires, among other things, base‐pairing interactions between a conserved spacer element in the pre‐mRNA and the minor U7 snRNA present as U7 snRNP. An oligonucleotide complementary to the first 16 nucleotides of U7 RNA can be used to characterize U7 snRNPs from nuclear extracts by native gel electrophoresis. Using similar native gel techniques, we present direct biochemical evidence for a stable association between histone pre‐mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
56
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 24 publications
3
56
0
Order By: Relevance
“…Bars represent the average of two or three measurements. Half-lives longer than 3 h (for ribonucleotide reductase, thymidine kinase, proliferating-cell nuclear antigen, and cyclin B1) are extrapolations, because in vitro decay rates are not linear after several hours (55a (34,40,44,72,73,75). The stem-loop region is particularly relevant to histone mRNA degradation for two reasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bars represent the average of two or three measurements. Half-lives longer than 3 h (for ribonucleotide reductase, thymidine kinase, proliferating-cell nuclear antigen, and cyclin B1) are extrapolations, because in vitro decay rates are not linear after several hours (55a (34,40,44,72,73,75). The stem-loop region is particularly relevant to histone mRNA degradation for two reasons.…”
Section: Discussionmentioning
confidence: 99%
“…The stem-loop is essential for proper cell cycle regulation and is the site at which mRNA degradation begins (4,14,29,31,39,47,56,57,65,68,75). It is also a binding site for a unique stemloop binding protein (40,46,72,73,76). In our cell-free mRNA decay system, three factors are required to destabilize polysome-associated histone mRNA: polysomes, histones, and S130.…”
mentioning
confidence: 99%
“…Processing of histone pre-mRNAs whose HDE has a relatively weak complementarity to U7 snRNA strongly depends on SLBP. On the other hand, substrates that form strong duplexes with the U7 snRNA can be processed in vitro with a significant efficiency in the absence of SLBP Melin et al, 1992;Spycher et al, 1994;Streit et al, 1993). Under in vivo conditions, SLBP is likely to be an essential factor in processing of all histone pre-mRNAs regardless of the HDE sequence and the extent of base pairing to the U7 snRNA (Pandey et al, 1994).…”
Section: Stem-loop Binding Protein (Slbp)mentioning
confidence: 99%
“…A number of in vitro studies have demonstrated that the role of SLBP in processing is to stabilize binding of U7 snRNP to the HDE Melin et al, 1992;Spycher et al, 1994;Streit et al, 1993). The importance of SLBP in 3' end processing depends on the type of histone pre-mRNA used in the assay.…”
Section: Stem-loop Binding Protein (Slbp)mentioning
confidence: 99%
“…Because the replication-dependent histone genes do not have introns, the only processing reaction required for the formation of mature histone mRNA is cleavage to form the 3' end. Processing of the 3' end of histone mRNA requires two cis elements, the stem-loop that interacts with a factor termed the hairpin binding factor (HBF) (Mowry and Steitz 1987a;Vasserot et al 1989;Melin et al 1992), and a purine-rich sequence located 9-14 nucleotides 3' of the stem-loop that binds the U7 small nuclear ribonucleoprotein particle (snRNP) (Mowry and Steitz 1987b;Cotten et al 1988;Soldati and Schiimperli 1988;Bond et al 1991). In addition to these two trans-acting factors, there is a heat-labile factor that has not been well characterized (Gick et al 1987).…”
mentioning
confidence: 99%